Isolated metastasis of skin melanoma to the spleen - Brzychczy, Andrzej; Wysocki, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2000)
Isolated splenic metastases of melanoma to the spleen are extremely rare. We present a case of 60 year old male patient admitted 20 months earlier to the removal of cutaneous melanoma followed by axillar lymphadenectomy. The remission after splenectomy was 40 month.